Trajetória do centro de pressão de crianças com paralisia cerebral durante o andar a cavalo: implicações terapêuticas - Meincke, Natiéle de Moraes (2020)
Cerebral Palsy (CP) is the most common cause of physical disability in childhood, whose greatest difficulties faced is obtaining adequate posture control. Among the rehabilitation strategies for postural control, Hippotherapy stands out, whose essence focuses on the task of riding a horse, which produces a therapeutic effect through the locomotor and sensory impulses transmitted by the horse's back to the patient, demanding postural control. Objectives: To verify if the trajectory of the pressure center (COP) on the saddle in a seated position changes over the 30 minutes of horse riding in children with CP, beyond to verify if the proprioceptive sensory manipulation of the static sitting position on the horse demands greater postural control than the same situation on the table, immediately before and after the horse riding activity. Methods: Descriptive research, composed of 18 children with CP, from 4 to 12 years old, with experience in horse riding. The dynamic assessments of the COP were measured over the 30 minutes of horse riding, in the minutes: 1, 5, 10, 15, 20, 25 and 30. Static assessments of the COP were carried out with the children sitting quietly on a table and mounted before and after riding the horse. Results: In the dynamic analysis, there were no significant differences over the 30 minutes in any of the investigated variables. In static evaluations sitting quietly, when compared on the table and mounted on the pre-walking horse, they showed significant differences, COPap, COPml, COPvel, RMSap and COParea greater on the horse, p ≤ 0.004, p ≤ 0.032, p ≤0.053, p ≤0.009 and p ≤≤ 0.001, respectively, in addition to also finding COPvelap p ≤ 0.035 and COParea p ≤ 0.013 larger post-gait riding on the horse. Conclusion: The children investigated demonstrated the ability to maintain postural control unchanged throughout the activity of horse riding. Greater oscillations in static assessments in the sitting condition occurred when the support base was manipulated, being greater on the horse.